2016
DOI: 10.1159/000444452
|View full text |Cite
|
Sign up to set email alerts
|

Isobolographic Analysis of Interaction for Three-Drug Combination of Carbamazepine, Phenobarbital and Topiramate in the Mouse Maximal Electroshock-Induced Seizure Model

Abstract: Background/Aims: To characterize the anticonvulsant effects of a combination of 3 antiepileptic drugs (AEDs; i.e. carbamazepine (CBZ), phenobarbital (PB) and topiramate (TPM)) at the fixed-ratio of 1:1:1 in the mouse maximal electroshock (MES)-induced seizure model. Methods: Tonic hind limb extension (seizure activity) was evoked in adult male albino Swiss mice by a current (sine-wave, 25 mA, 500 V, 50 Hz, 0.2 s stimulus duration) delivered via auricular electrodes. Type I isobolographic analysis for parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…28 The interaction among the 3 AEDs (LCM, LTG and PB) from this study can also be compared to the interactions observed previously for the combinations of LCM, carbamazepine (CBZ) and PB, 16 or topiramate (TPM), CBZ and PB, against maximal electroconvulsions in mice. 17 More specifically, a supra-additivity (synergy) for the combination of TPM, CBZ and PB was found in the MES test in mice. 17 In contrast, the replacement of TPM with LCM in the mixture of LCM, CBZ and PB resulted in additivity with a trend to sub-additivity in the MES test in mice.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…28 The interaction among the 3 AEDs (LCM, LTG and PB) from this study can also be compared to the interactions observed previously for the combinations of LCM, carbamazepine (CBZ) and PB, 16 or topiramate (TPM), CBZ and PB, against maximal electroconvulsions in mice. 17 More specifically, a supra-additivity (synergy) for the combination of TPM, CBZ and PB was found in the MES test in mice. 17 In contrast, the replacement of TPM with LCM in the mixture of LCM, CBZ and PB resulted in additivity with a trend to sub-additivity in the MES test in mice.…”
Section: Discussionmentioning
confidence: 97%
“…17 More specifically, a supra-additivity (synergy) for the combination of TPM, CBZ and PB was found in the MES test in mice. 17 In contrast, the replacement of TPM with LCM in the mixture of LCM, CBZ and PB resulted in additivity with a trend to sub-additivity in the MES test in mice. 16 On the other hand, the replacement of CBZ with LTG produced additivity without any trend to sub-additivity (antagonism) in the MES test, as documented in this study for LCM, LTG and PB.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations